Investigasi Struktur Gedung Balai Pertemuan Kelurahan Tlogosari Wetan - Hani Purwanti; Ferry Firmawan; Diah Aryati Puji Lestari (Jurnal Pengabdian KOLABORATIF, 2024)
The meeting hall building in Tlogosari Wetan Village consists of one floor extending throughout the land that is still surrounded by rice fields and is predominantly constructed with reinforced concrete materials. Based on information, the building has been standing for more than 20 years. Seeing this, the Community Service Team aims to investigate the condition of the structural system and materials of the Village Hall Building. To find out the condition of the structure and building materials, and can be a follow-up for partners to improve and utilize the building. The method used in this investigation is visual observation of structural conditions and non-destructive material testing. The results of the investigation show that a review of the compressive strength characteristics of the concrete in column elements still meets the requirements for earthquake-resistant concrete materials according to SNI 2847 2019.